The symbolic meanings and values in the Momayango Bele procession of the Gorontalo community and its implications on the learning of local wisdom in school - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2024)
This research is intended to obtain a description of (a) the meaning of verbal and nonverbal symbols of the values contained in the Momayango Bele process, (b) the meaning of nonverbal symbols in the Momayango Bele process, and (c) the implications for learning local wisdom in schools. The study employed a descriptive method with a type of qualitative research that is used to reveal and describe how the payango tradition determines people's houses in Gorontalo and the extent to which the payango tradition is applied as well as the stages of traditional procedures in building a house. The data were obtained from informants/speakers through the interview, the recording and observation of data obtained then analyzed. Based on the research results, the Momayango Bele procession is a process of measuring and making foundation patterns and laying the first stone for house building in the Gorontalo community. The symbols in the Momayango Bele procession contain complex and deep meanings. The impact of the Momayango Bele procession on the local community is to preserve their cultural identity.